IMPLEMENTATION OF RAHN ACADEMIC (SHARIA PAWN) IN SHARIA FINANCIAL INSTITUTIONS - Inda Husna Fatwa; Muammar Khaddafi (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2023)
The development of sharia-based products is increasingly prevalent in Indonesia, including pawn shops. Perum pawnshops issued sharia-based products called sharia pawnshops. Basically, sharia-based products have such characteristics, do not collect interest in various forms due to usury, determine money as a medium of exchange not as a commodity traded, and do business to obtain compensation for services and or profit sharing. This research includes the type of literature study by looking for theoretical references that are relevant to cases or problems found. Theoretical references are obtained by means of literature study research and then used as the basic foundation and main tools for analyzing data. The type of data used by the authors in this study is secondary data obtained from journals, books, documentation and the internet. The data that has been obtained is then analyzed using a descriptive analysis method of Islamic Pawnshop or known by the term rahn, in its operation using the Fee Based Income (FBI) or Mudharabah (profit sharing) method. Because customers using UP (UP) have different objectives, for example for consumption, paying school fees or additional working capital, the use of the Mudarabah method has not been used properly. Therefore, pawnshops use the Fee Based Income (FBI) method. the use of the Mudarabah method has not been used properly. Therefore, pawnshops use the Fee Based Income (FBI) method. the use of the Mudarabah method has not been used properly. Therefore, pawnshops use the Fee Based Income (FBI) method.